Affirmation of School Management and Success of Islamic Religious Education Learning - Kristo Paulus; Nur Irsyadiah; Ahmad Rifa’i (Syntax Corporation Indonesia, 2021)
School management is an activity that is carried out effectively and efficiently to improve school performance, including learning Islamic religious education. Therefore it is necessary to affirm that school management will be more organized and focused on goals. Schools that run a good managerial system will certainly pay attention to the quality of education in them so that learning in these schools will run optimally. The object of this research is Islamic education learning in schools with good school management. The research methodology used is qualitative research methods with descriptive methods. The findings in this study show that schools that carry out affirmation of school management will be able to encourage the success of Islamic Education learning in these schools.